American Literatures After 1865 - Peterson, Scott D.; Berke, Amy; Bleil, Robert (Open textbook library.)
This book is an anthology of American Literatures After 1865, a reimagining of the open educational resource: Writing the Nation: A Concise Introduction to American Literature 1865 to Present.